Outcome of Thrombolysis in Acute Myocardial Infarction in a Tertiary Care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The main purpose of thrombolysis in acute myocardial infarction is early and complete reperfusion. Incomplete or delayed thrombolysis is associated with an increased risk of death and left ventricular dysfunction. The time to reperfusion and complete reperfusion remain the key determinants for appropriate outcome of cardiovascular events.Objective: To find out the effect of thrombolytic therapy and its outcome in relation with timing of thrombolysis and associated risk factors in ST elevated myocardial infarction (STEMI) patients.Materials and Methods: This cross-sectional interventional study was carried out in combined military hospital, Dhaka from July 2017 to May 2018. Total 85 patients of acute STEMI having specified criteria were selected and treated with Streptokinase at a dose of 1.5 million units diluted in 100 mL normal saline. Twelve-lead ECG was recorded immediately before the start of thrombolytic therapy and 180 min afterwards.Results: Among 85 STEMI patients 65 were male and the age range was 40-80 years. Sixty nine patients (81.2%) underwent thrombolysis within 12 hours of onset of chest pain among them complete resolution of ST segment occurs in 45(65.2%) patients while 16 patients (18.8%) received thrombolysis after 12 hours among them complete resolution occurs only in 7(43.8%) patients.  Fully reperfused patients have no complications. Patients having diabetes mellitus, presented with atypical chest pain and received thrombolytic therapy after 12 hours had various types of complication.Conclusion: STEMI patients received thrombolysis therapy within 12 hours of onset of chest pain responded well to thrombolytic therapy.Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 42-44